On-Surface Synthesis and Characterization of a Cycloarene: C108 Graphene Ring - Fan, Qitang; Martin-Jimenez, Daniel; Werner, Simon; Ebeling, Daniel; Koehler, Tabea; Vollgraff, Tobias; Sundermeyer, Jörg; Hieringer, Wolfgang; Schirmeisen, André; Gottfried, J. Michael (Journal of the American Chemical Society, 2020)
The synthesis of cycloarenes in solution is challenging because of their low solubility and the often hindered cyclodehydrogenation reaction of their nonplanar precursors. Using an alternative on-surface synthesis protocol, we achieved an unprecedented double-stranded hexagonal cycloarene containing 108 sp2 carbon atoms. Its synthesis is based on hierarchical Ullmann coupling and cyclodehydrogenation of a specially designed precursor on a Au(111) surface. The structure and other properties of the cycloarene are investigated by scanning tunneling microscopy/spectroscopy, atomic force microscopy, and density functional theory calculations.
CRIS-Team Scopus Importer:2020-01-24